The Economists and Monetary Thought in Interwar New Zealand: The Gradual Emergence of Monetary Policy Activism - Geoffrey Brooke; Anthony Endres; Alan Rogers (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2018)
In spite of the existence of several monetary and central bank histories, the emergence of monetary thought in New Zealand after 1914 has not been subject to extensive analysis. This paper remedies this deficit for the interwar period. The focus is upon the propagation of monetary ideas in New Zealand and their intellectual sources. We apply a heuristic in which different monetary doctrines are situated along a continuum between extreme monetary policy 'activism' and extreme 'minimalism'. In the 1920s, New Zealand economists betrayed a minimalist bias across several dimensions: money supply regulation, the role of money and the international monetary transmission process in the business cycle, and the operation of bank-credit allocation mechanisms. Incipient activism in the work of Condliffe and Belshaw was countered by Niemeyer's case for a minimalist central bank. Fisher adopted an anti-reflationist, forced savings approach to the 1930s crisis; he underscored the deleterious monetary and real consequences of Government exchange rate management after 1933. Copland, Tocker, Belshaw and Hight downplayed these consequences. Extended debate over the original Reserve Bank legislation and perennial amendments thereafter, generated new meanings for the phrase 'monetary policy independence'; it also turned most economists against extreme activism (or the policy of monetary nationalism) that prevailed from 1938. Throughout the interwar period, New Zealand entertained a vigorous contest of monetary ideas; most of those ideas were inherited from the work of Keynes (as early as 1923), Hawtrey, Cannan, Robbins, and Hayek, though adapted to local conditions.
Keywords: 330; New Zealand; population policy; migration; history of thought